Back to the future: Forgotten protocols for optimizing the isolation of arthropod haemocytes - Norman Ratcliffe (Developmental and Comparative Immunology, 2024)
Consideration is given to previous and more recent protocols for harvesting arthropod haemocytes from Galleria, Drosophila, mosquitoes, Limulus and crustaceans. The optimal harvesting of these cells is essential for meaningful studies of invertebrate immunity in vitro. The results of such experiments, however, have often been flawed due to a lack of understanding of the fragile nature of arthropod haemocytes on exposure to bacterial lipopolysaccharides, resulting in the aggregation and loss of cell types during haemolymph clotting. This article emphasizes that although there are similarities between mammalian neutrophils and arthropod haemocytes, the protocols required for the successful harvesting of these cells vary significantly. The various stages for the successful harvesting of arthropod haemocytes are described in detail and should provide invaluable advice to those requiring both high cell viability and recovery of the different cell types for subsequent experimentation.